sin(x + dx) = sinxcosdx + sindxcosx
d(sinx) / dx = ( (sinxcosdx + sindxcosx) - sinx ) / dx
As dx very small
sindx = dx
cosdx = 1
Therefore:
d(sinx) / dx = ( (sinx(1) + dx cosx) - sinx ) / dx
= (sinx - sinx + dx cosx) / dx
= dx cosx / dx
= cosx
2006-12-20 06:20:17
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
The answer primarily lies in limit laws. The two limits you need to know are:
1) lim (x -> 0, sin(x)/x) = 1, and
2) lim (x -> 0, (cos(x) - 1)/x = 0.
You would also need to know the sine addition law;
sin(a + b) = sin(a)cos(b) + sin(b)cos(a).
Let's start the proof.
Let f(x) = sin(x)
f'(x) = lim { f(x + h) - f(x) } / h
h -> 0
lim { sin(x + h) - sin(x) } / h
h -> 0
lim { [sinxcosh + sinhcosx] - [sinx] } / h
h -> 0
Rearranging the terms, i.e moving sinx between the two terms in the first set of brackets,
lim { [sinxcosh - sinx] + sinhcosx] } / h
h -> 0
Now, we can split this up into two separate limits and two fractions.
lim { [sinxcosh - sinx] } / h + lim (h -> 0, sinhcosx)/h
h -> 0
Due to text constraints, I'm going to work these limits out individually. I'll call the first limit A and the second limit B, and our answer should be A + B.
A = lim { [sinxcosh - sinx] } / h
h -> 0
Remember that h is our limit variable, and everything else is treated as a constant. This means we can effectively factor sin(x) out of the entire limit.
A = sin(x) * lim (h -> 0, [cosh - 1]/h)
But remember that we establishd that this limit is equal to 0. Therefore,
A = sin(x) * 0 = 0
B = lim (sinhcosx/h)
h -> 0
We can factor out cos(x) out of the limit because it's consider a constant (and there are NO h terms in there.
B = cos(x) * lim (h -> 0, sinh/h)
But remember, that we established right at the start that this limit is equal to 1. Therefore
B = cos(x) * 1 = cos(x)
The whole limit is equal to A + B, or
0 + cos(x) = cos(x).
Therefore, the derivative of sin(x) is cos(x).
As you can see, it was imperative that we used these two facts:
1) lim (x -> 0, sin(x)/x) = 1, and
2) lim (x -> 0, (cos(x) - 1)/x = 0
The actual proof of these two limits involves something called the Squeeze Theorem, and the only part of the proof I omitted was the details of why the above 2 limits are true.
2006-12-20 14:24:25
·
answer #2
·
answered by Puggy 7
·
1⤊
0⤋
An easy way is to look at the taylor series of sinx around 0 and take the derivative of this infinite polynomial and you will find the taylor series for cos x.
2006-12-20 15:22:23
·
answer #3
·
answered by Topologist 1
·
0⤊
0⤋
let y=sinx
y+delta y=sin(x+deltax)
where a small increment of delta x in xresults in a small increment of delta y in y
y+delta y-y=sin(x+delta x)-sinx
delta y=2cos(x+deltax/2)sin(delta x/2)
dividing both sides by delta x and allowing delta x to tend to zero
lim.delta x tending to zerodelta y/delta x
=limit delta x tending to zero 2cos(x+deltax/2)sin(deltax/2)/deltax
the LHS id dy/dx by definition
the RHS=lim delta x tending to zero cos(x+deltax/2)sindeltax/2/deltax/2
=cosx
2006-12-20 14:22:20
·
answer #4
·
answered by raj 7
·
0⤊
0⤋
There are a number of ways to do this.
One is to use the identity that
sinx = (e^ix - e^-ix)/2 and differentiate that.
2006-12-20 14:13:56
·
answer #5
·
answered by firefly 6
·
0⤊
0⤋
The definition of derivate is:
df(x) = lÃm..... f(x+Îx) - f(x)
dx....... Îxâ0........Îx
using that for the sin:
d (sinx) = lÃm..... sin(x+Îx) - sinx
dx .......... Îxâ0...........Îx
sin(a+b) = sina*cosb + cosa*sinb
then:
sin(x+Îx) = sinx*cos(Îx) + cosx*sin(Îx)
by substitution:
d (sinx) = lÃm...... sinx*cos(Îx) + cosx*sin(Îx) - sinx
dx............Îxâ0 ...................... Îx
agroupping:
d (sinx) = lÃm....... cosx*sin(Îx) - sinx (1 - cos(Îx))
dx............ Îxâ0.................... Îx
arranging in fractions:
d (sinx) = lÃm ...... / cosx *. /sin(Îx)\ - sinx *. /.1 - cos(Îx) \ \
dx ............Îxâ0.. \...........\ .. Îx ./..............\........ Îx .. / /
d (sinx) =. cosx * lÃm ... /sin(Îx)\ - sinx * lÃm... /.1 - cos(Îx).\
dx.....................Îxâ0 \ ..Îx.. /............Îxâ0\...... Îx ...... /
This lÃmits have by definition this values:
. lÃm ... /sin(Îx)\ = 1
Îxâ0 \... Îx.../
. lÃm ... /.1 - cos(Îx) \ = 0
Îxâ0.. \...... Îx ..... /
then:
d (sinx) = cosx * 1 - sinx * 0
dx
finally
d (sinx) = cosx
dx
2006-12-20 14:56:27
·
answer #6
·
answered by ProzeB 2
·
0⤊
0⤋